GAME EDUKASI WAYANG: INOVASI PELAKSANAAN PENDIDIKAN KARAKTER BAGI SISWA SEKOLAH DASAR DI ERA DIGITAL - Irhas; Asrowi; Djono (Jurnal Utilitas, 2022)
This paper aims to describe the importance of internalizing character education through media that is appropriate to the development of ICT and student characteristics. Considering several facts revealing that the achievement of the internalization of character education in schools is still relatively low, given the low interest in student learning and the use of learning media that tends to be static, whereas in learning in the digital era where students are familiar with the use of technology, of course, it must receive attention given the great potential if opportunities for using ICT in the learning process can be optimized. This paper uses a descriptive qualitative design approach with a literature review method, data is collected from the results of reading orientation of authentic sources namely books, journals and relevant literature and analyzed through reduction, display and verification as conclusions. Internalization of character education in the digital era requires the integration and synergy of ICT, the existence of ICT packaged in the form of educational games will be able to create greater opportunities in optimizing the internalization of character education based on local wisdom, such as Wayang.